Analysis of Lao PDR’s Policy The Successful Policy of Lao PDR’s Policy on Responding COVID-19 - Nisa, Aprilia Chairun; Rhasintya, Monica; Pangestu, Zeffa Alifah (Journal of ASEAN Dynamics and Beyond, 2020)
Coronavirus is a new type of virus, which until now has infected various countries throughout the world. Laos is also one of the countries affected by the pandemic and became one of the countries in Southeast Asia that managed to deal without swallowing a single death. This research aims to find out how the Laos government responds to the COVID-19 pandemic and explains the impact of the policies that were put in place during the pandemic. This study uses qualitative research methods with primary data obtained through search results in journals, documents, and official websites. This study provides the result that the Government of Laos is considered successful in dealing with COVID-19 by implementing several policies that are divided into 4 fields; economy, education, health, and travel. The research results also show that the policy is not only tangible success but also a decline in several fields, namely economic and social.